2016
DOI: 10.4314/ujas.v16i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of etiological agents (Liberibacter spp.) associated with citrus greening disease in Uganda

Abstract: Citrus Huanglongbing (HLB), commonly referred to as citrus greening, is one of the major disease challenges of citrus. In Uganda, there was limited information on Liberibacter spp., the causal organisms of HLB disease, and its psyllid vectors despite the presence of HLB symptoms on citrus. The objective of this study was to identify the Liberibacter spp. and psylla vector species responsible for HLB in Uganda. Other native plant species that could be hosts to pathogens and the psyllid vectors, but are not in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…We identified both Laf and LafCl in Uganda; the two Liberibacter previously found to be widely distributed in the citrus-growing areas in the western and central regions of the country 27 . In our study, LafCl was dominant in the eastern region of the country where Las had been previously misreported 25 . Our results support the hypothesis that the previous record of Las in Uganda was probably a misidentification 27 therefore, the presence of Las in Uganda remains unconfirmed.…”
Section: Discussionsupporting
confidence: 46%
“…We identified both Laf and LafCl in Uganda; the two Liberibacter previously found to be widely distributed in the citrus-growing areas in the western and central regions of the country 27 . In our study, LafCl was dominant in the eastern region of the country where Las had been previously misreported 25 . Our results support the hypothesis that the previous record of Las in Uganda was probably a misidentification 27 therefore, the presence of Las in Uganda remains unconfirmed.…”
Section: Discussionsupporting
confidence: 46%
“…However, from molecular research by Khamis et al (), these psyllid species on S. abyssinica were grouped into ACT. Similarly, Kalyebi et al () claimed to have found ACT on S. abyssinica in Uganda based purely on presence of pit galls. Moreover, a study by Abate () on identity and bionomics of insect vectors of tristeza and greening diseases of citrus in Ethiopia found and grouped psyllids on S. abyssinica and other non‐rutaceae plants into ACT.…”
Section: Discussionmentioning
confidence: 94%
“…The predicted optimal areas for the establishment of Las were the same areas where the pathogen was found in previous studies (Ajene et al, 2019; Saponari et al, 2010). In 2016, the presence of Las was reported in Uganda (Kalyebi et al, 2016). However, the presence points from Uganda were not included in the models as the report was shown to be a misidentification of LafCl (Roberts et al, (2017).…”
Section: Discussionmentioning
confidence: 99%